Antibiogram and heavy metal resistance of streptococcus spp. on tilapia (Oreochromis sp.) - Nor Mahirah Tajuddin (2016)
This study deal with the antibiogram and heavy metal resistance of Streptococcus spp. on Tilapia (oreochromis sp.) in Jeli area. 12 sample had successfully isolate and identify from tilapia ﬁsh. Antibiotic susceptibility test was carried out by using disk diffusion method against l7 antibiotics to determine susceptibility, intermediate and resistant of Streptococcus spp. the tested antibiotic were The susceptibility of Streptococcus spp. isolated from Tilapia, Oreochromis niloticus showing that 44.79% was susceptible, 11.98% was intermediate and 43.23% was resistant to Streptococcus spp. Oxytetracyline, ﬂorfenicol, and oleandomycin showing the highest percentage in susceptible of the streptococcus while amoxycilin. penicillin G and ampicilin showing resistant to the bacteria. The MAR index test in this study was 0.4 indicate that the Tilapia was highly exposed to the tested antibiotic. For the heavy metal test, cadmium, copper and chromium were tested in identifying the resistant to the bacteria. ln this study, cadmium and chromium showing resistant to the bacteria while copper show sensitive to the bacteria. This study also undergoes antimicrobial activity of grapehene oxide (GO) toward Streptococcus spp. On this study, GO suspensions showing that 68% cases were sensitive while 32% were resistant toward Streptococcus spp.